Diagnostic value of panoramic indices to predict osteoporosis and osteopenia in postmenopausal women - Somayeh Nemati; Zahra Dalili Kajan; Bardia Vadiati Saberi; Zohre Arzin; Mohammad Hashem Erfani (Wolters Kluwer Medknow Publications, 2016)
Background: Osteoporosis is characterized by the progressive loss of bone density, which leads to severe fractures. This study conducted to evaluate the diagnostic value of the mandibular radiomorphometric indices of panoramic radiographs to predict the status of bone mineral density (BMD) in postmenopausal women. Materials and Methods: Panoramic radiographs of ninety postmenopausal women (thirty osteoporotic, thirty osteopenic, and thirty controls) with the mean age of 54.47 years were evaluated. Bone densitometry was performed by using the dual-energy X-ray absorptiometry method. Variables such as the mandibular cortical width (MCW), panoramic mandibular index (PMI), gonial angle, mandibular cortical index (MCI), and the number of teeth lost were assessed. Results: The average of MCW in normal, osteopenic, and osteoporotic groups were 4.56, 3.97, and 3.39 mm, respectively. The PMI in normal, osteopenic, and osteoporotic groups was calculated as 0.33, 0.28, and 0.24, respectively. The MCW, PMI, and the number of teeth lost in the three groups showed statistically significant differences (P = 0.0001). The MCI had a significant difference in the three groups (P = 0.0001). The optimal cutoff points for MCW and PMI to predict low BMD were 4.13 mm and 0.29, respectively. Conclusions: The MCW, PMI, and MCI have a high diagnostic value to predict low BMD. By increasing the age and the postmenopausal duration, MCW and PMI decrease, whereas C3 form of MCI and the number of teeth lost showed increase. About 1 mm decrease in MCW increased the odds of reduced BMD (osteoporosis, osteopenia) up to 3.22-fold.